Assessment of Soil Quality for a Semi-Arid Irrigated Under Citrus Orchard : Case of the Haouz Plain, Morocco - Sefiani, Salma; El Mandour, Abdennabi; Laftouhi, Nour-Eddine; Khalil, Nourddine; Kamal, Safia; Jarlan, Lionel; Chehbouni, Abdelghani; Hanich, Lahoucine; Khabba, Said; Hamaoui, Addi (European Scientific Journal, ESJ, 2017)
The irrigated perimeter of the Haouz plain is one of the largest in Morocco with 310.000 Ha with intense agricultural practices based on irrigation. Besides, recent studies have shown that the aquifer is characterized by an overall average to low sensitivity and vulnerability. The objective of this study is to provide an in depth diagnosis of the current situation regarding soil quality for a drip irrigation area: a citrus orchard, in a farm named Agafay, is located in the western part of Haouz, at 35 km SW of Marrakesh. To this objective, an intensive in situ campaign has been carried out focused on the measurements of the physico-chemical parameters of soil, at nine plots. The variation of these parameters, their impact on the type of rootstock and the variation of pollutants through the five soil horizons are analyzed. The results revealed that the condition in the soil quality is not very alarming. As most of the soils are light-textured, with poor organic matter content and basic to very basic pH. The reduction of organic matter, salinity, orthophosphates and nitrates with depth is attributed to the localized mode of irrigation adopted at the site which minimizes the loss of nutrients and, in fine, pollution of the aquifer. Multivariate analysis shows that the total and lime correlate well with the pH, which in turn correlate negatively with nitrate content and soil electrical conductivity. This work has strong implications for the quality assessment of soil for all irrigated perimeters by the drip in semi-arid areas, order to ensure the conservation and sustainability of the production system.